Antibiotic Resistance Pattern in Urinary Tract Infection during Pregnancy in South Indian Population - Suresh, Dr. Aneena (Asian Journal of Pharmaceutics (AJP), 2018)
Background: One of the most common complications during pregnancy is urinary tract infection (UTI) which can be either symptomatic or asymptomatic. Symptomatic bacteriuria occurs in 2%–7% of pregnant women in the first trimester and asymptomatic bacteriuria occurs in 5–10%; 20–30% of which progress to pyelonephritis if left untreated. There was a 50% increase in the risk of low birth weight and a significant increase in pre-term delivery, pre-eclampsia in pregnant women with bacteriuria. Safest antibiotics used in pregnancy are nitrofurantoin, cephalosporin, penicillin, and fosfomycin trometamol. With the emergence of drug resistance among the Gram-negative and Gram-positive bacteria, the choice of drugs for the treatment of UTI is very limited. Objective: The purpose of our study was to find out the antibiotic resistance pattern in UTI during pregnancy with the common causative organism, their antimicrobial sensitivity and resistance pattern. This study will help in choosing the most effective antibiotic for the treatment of UTI in pregnancy. Materials and Methods: Urine samples were subjected to microscopy and those found positive of UTI were inoculated in nutrient agar to confirm the presence of microorganisms. This was followed by streaking in HI chrome and McConkey agar. Identification was done using Gram staining and biochemical tests. Antibiotic resistance was evaluated using Kirby–Bauer disk diffusion method. Results: The most common causative organism was found to be Escherichia coli. Nitrofurantoin showed the highest sensitivity toward all the organisms.